Sex Differences in the Behavioural Outcomes of Prenatal Nicotine and Tobacco Exposure - Sikic, Anita; Frie, Jude A.; Khokhar, Jibran Y.; Murray, Jennifer E. (Frontiers in Neuroscience, 2022)
Smoking remains the leading cause of preventable death worldwide. A combination of biological and environmental risk factors make women especially vulnerable to nicotine addiction, making it harder for them to quit smoking. Smoking during pregnancy, therefore, is still a major health concern, with epidemiological data suggesting a role for gestational nicotine exposure in the development of several behavioral disorders. Given there are significant sex-specific behavioural outcomes related to smoking in adolescence and adulthood, it is probable that the behavioural outcomes following gestational nicotine or tobacco exposure are similarly sex-dependent. This is an especially relevant topic as the current landscape of nicotine use shifts toward vaping, a mode of high doses of nicotine delivery that is largely believed to be a safer alternative to cigarettes among the public as well as among pregnant women. Here we review existing clinical and preclinical findings regarding the sex-dependent behavioural outcomes of prenatal nicotine exposure. We also highlight the challenges within this literature, particularly those areas in which further research is necessary to improve consistency within, and between, clinical and preclinical findings.